Aspects of the therapeutic approach to vulvovaginal candidiasis - Anjos, Genivaldo Alves dos; Pereira, Vinicius Soares; Hori, Juliana Issa; Rodrigues, Andressa Romualdo (Seven Editora, 2023)
Vulvovaginal candidiasis is an infection of the vulva and vagina caused by various types of Candida spp. This condition affects 75% of all women at least once in their lifetime, occurring more frequently during their childbearing years. The transmission of this fungal infection occurs through contact with mucous membranes and secretions on the skin of patients or patients, sexual contact, contaminated water and vertical transmission. Some other characteristic symptoms more seen in cases of VVC are white, creamy and flat lesions, being more intense in the premenstrual period, when the vaginal acidity increases. numerous antifungals are available on the market which are available for oral administration in tablet form or, for topical use, in the form of creams, lotions, vaginal tablets, suppositories and coated tampons. The general objective of the work was to analyze, through a literature review, conventional and alternative treatments for the therapeutic approach of Vulvovaginal Candidiasis in its context, using definitions, epidemiological data and its symptoms in society. The present work is an integrative review, which had data collection carried out from March 2021 to October 2021 in the Lilacs, Scielo, Google academic databases. The search resulted in 902 articles, of which 14 met the inclusion criteria. The search for treatments against vulvovaginal candidiasis has been shown to be wide according to the selected articles. We conclude that the vulvovaginal candidiasis pathology has been showing resistance in some therapeutic approaches, as well as some women do not adhere to any type of treatment, due to lack of knowledge about the pathology. DOI:https://doi.org/10.56238/uniknowindevolp-132